Vitamin C Improves the Efficacy of Oxytetracycline in Treatment of Aeromonas hydrophila-infected Juvenile Catfish (Clarias gariepinus) - Afisu Basiru; Abdulateef Abiodun Ajadi; Olayiwola Akeem Ahmed; Kolawole Yusuf Suleiman; Saliu Akanni Ameen (Department of Aquaculture, 2022)
The recent global increase in demand for catfish products has led to intensive catfish farming, favoring Aeromonas infections. Therefore, there is a need to enhance the current management method of Aeromonas infection in catfish. This study evaluated the efficacy of adding vitamin C to Oxytetracycline in the treatment of Aeromonas infection through the development of skin lesions, mortality and serum antioxidant defense system. One hundred and five juvenile catfish were randomly assigned to seven groups (n=15). The first group served as control and was neither infected nor treated, while the other groups were infected with Aeromonas hydrophila. Seventy-two hours after inoculation, catfish in groups 2-7 were treated as follows: no treatment, Oxytetracycline through bath, Oxytetracycline through feed, Oxytetracycline through bath with 500 mg of vitamin C in water, Oxytetracycline through feed with 500 mg of vitamin C in water and 500 mg of vitamin C only in water, respectively. The treatment was done for five consecutive days. Behavioral changes, clinical signs and mortality were observed. Data were presented as Mean±SD and analyzed using descriptive statistics or One-way Analysis of Variance (ANOVA) and Tukey's Test. p <0.5 were regarded as significant. The cumulative percentage mortality in groups (Groups 5 and 6) supplemented with Vitamin C was 26.7 and 33.3 compared to 90% and 46.6% in groups 2 and 4, respectively. The results showed that adding vitamin C to Oxytetracycline reduced the development of skin lesions and mortality. Therefore, Vitamin C is recommended to manage Aeromonas hydrophila infection in catfish.